Cyberbullying di Media Sosial: Studi Netnografi Komentar Netizen di Akun TikTok @garutupdate_ - Abde Rizky Supriadi; Zikri Fachrul Nurhadi; Annisa Husnusyifa (MUKASI: Jurnal Ilmu Komunikasi, 2025)
This research is motivated by the widespread use of TikTok as a popular social platform in Indonesia, which simultaneously presents the phenomenon of cyberbullying in the comments column of popular accounts such as @garutupdate. This research aims to reveal how the phenomenon of cyberbullying emerges and develops in the comment section of the TikTok account @garutupdate_, as well as the factors influencing interaction patterns among netizens in this digital space. Data collection techniques in research use observation, interviews, literature studies and documentation. Using a netnographic method, the researcher observed the online community’s activities, analyzed comments, and conducted interviews with active users to gain deeper insight into the dimensions of culture, interaction, online traces, and engagement. The findings show that local culture, spontaneous habits, and a high level of tolerance toward negative comments are the main triggers for the emergence of cyberbullying behaviors. This research focuses on cyberbullying practices on the local TikTok news account garutupdate, presenting novelty through an analysis of the influence of local content and regional languages ​​in shaping and normalizing cyberbullying patterns in the Garut community. Findings indicate the dominance of sarcasm, appearance-based insults, and racially and ethnically biased comments expressed through local terms and emojis, supported by a casual, go-with-the-flow culture and tolerance of negative comments, so that these behaviors are considered normal despite their psychological impact on victims. The research highlights the urgency of digital literacy and active moderation to create a healthy discussion space on local platforms.